India-China Borderlands : Conversations Beyond the Centre. - Kurian, Nimmi (SAGE Publications, 2014)
The India-China borderlands have remained largely in a freeze frame, awaiting a new political imagination that has been a long time coming. This book offers a critical comparative analysis of India-China relations at the subregional level, an analytical level that remains an understudied aspect in both research and policy. The study situates their evolving dynamics within the rubric of the massive state-led developmental thrust that India's Northeast and China's western border regions are currently witnessing. By and large, India an.